Aspectos jurídicos da compensação financeira pela exploração de recursos minerais - CFEM - Silveira, Renata Abrantes da (2010)
The objective of this dissertation is to discuss the scope the statement prescribed by § 1 of Article 20 of the Federal Constitution, which ensured the States, the Federal District and municipalities, as well as the direct administration offices of the Union, under the law, a participation in the outcome of the exploitation of mineral resources in its territory or financial compensation for such exploitation. The aim is to define the institutions known as Financial Compensation for the Exploration of Minerals - CFEM, Public Participation in the result of exploitation of mineral resources and the called Royalty, seeking to trace the legal law and the legal regime that is to be applied to each institute. It examines the laws that regulated the infra constitutional statement mentioned above, and set up the financial burden called Financial Compensation for Exploiting Mineral Resources - CFEM. Thus, it was as defined positive law system as an object of study, demonstrating, however, essential to address the integration of various sub-legal, as the subsystem of Environmental Law, the Mining Law, the Financial Law, Tax Law, among others. Finally, we conclude that the infraconstitutional legislature established an real participation by the exploitation of mineral resources, asset of original patrimonial revenue, Institute of Financial Law. However, by constitutional mandate, these revenues are distributed directly to federal entities, therefore for them this is transferred revenue